Characterization of nature dye-sensitized solar cell (DSSC) based on nanocrystalline titanium dioxide - Gomesh Nair Shasidharan (School of Electrical Systems Engineering, Universiti Malaysia Perlis, 2015)
This thesis focuses on fabricating dye sensitized solar cell (DSSC) with anatase and rutile-anatase mixture of titanium dioxide (TiO2) electrode at varied thickness. The electrode is the sensitized with nature based dyes from fruits, plants and flower and finally the investigation on an alternative counter electrode catalytic material from carbon sources.